EFFECT OF LEAF NUTRITION WITH LIQUID NITROGEN FERTILIZERS ON THE DEVELOPMENT PHASES OF WINTER WHEAT (Scientific journal of the Fergana State University, 2025)
This article aims to achieve a high-quality grain yield by improving winter wheat cultivation agrotechnologies of foliar feeding of liquid nitrogen fertilizers to increase winter wheat productivity and grain quality.